Cash Transfer Programs and Household Labor Supply - Daniela Del Boca; Chiara D. Pronzato; Giuseppe Sorrenti (Institute of Labor Economics (IZA), 2020)
Employment helps reduce the risk of poverty. Through a randomized controlled trial, we evaluate the impact of a conditional cash transfer (CCT) program to low-income families with dependent children on household members' labor supply. Recipients are required to attend labor-market-oriented mentoring courses as a condition of the transfer. One year after admission to the program, fathers assigned to the CCT program are more likely to work (+14 percent) than fathers assigned to an unconditional cash transfer program or to a pure control group. No effect arises for mothers. Results seem to be explained by improved family networks and increased parental investments in activities that enhance labor market opportunities.
Keywords: I10; I20; J24; I31; 330; conditional cash transfers; poverty; household labor supply; mentoring courses